The Polytopic-k-Step Fibonacci Sequences in Finite Groups - Ömür Deveci (Discrete Dynamics in Nature and Society)
We study the polytopic-k-step Fibonacci sequences, the polytopic-k-step Fibonacci sequences modulo m, and the polytopic-k-step Fibonacci sequences in finite groups. Also, we examine the periods of the polytopic-k-step Fibonacci sequences in semidihedral group SD2m.